Numerical study of carrier reservoir semiconductor optical amplifier-based all-optical XOR logic gate. Issue 3 (6th February 2021) - Kotb, Amer; Zoiros, Kyriakos E.; Li, Wei
Abstract : The long carrier lifetime of the semiconductor optical amplifier (SOA) limits its operation speed and exploitation as ultrafast nonlinear switching element. Therefore, an alternative SOA with a faster carrier lifetime is desired for high speed photonic applications. In this paper, we employ the carrier reservoir SOA (CR-SOA) for the first time to demonstrate through simulations the feasibility of all-optical exclusive-OR (XOR) logic gate at 100 Gb/s. For this purpose, a pair of CR-SOAs are incorporated in a Mach-Zehnder Interferometer. The variation of the quality factor (QF) against the key operating parameters is examined for both CR-SOAs- and conventional SOAs-based XOR gate at 100 Gb/s, including the effect of amplified spontaneous emission. The results show that not only higher but also acceptable QF is obtained at 100 Gb/s only when using CR-SOAscompared to conventional bulk SOAs, i.e. QF = 18.5 versus 3.3, respectively.